2015
DOI: 10.1002/bjs.9688
|View full text |Cite
|
Sign up to set email alerts
|

Randomized clinical trial of autologous skin cell suspension combined with skin grafting for chronic wounds

Abstract: Background: Treatment of chronic wounds using traditional surgical procedures is challenging because of the low graft take rates. This study investigated the combination approach of split-thickness autografts with harvested skin cell suspension for chronic wound treatment. Click here to watch video footage recorded by the author about the contents of this paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 22 publications
0
51
0
Order By: Relevance
“…Autologous skin cell suspension enables delivery of viable keratinocytes, fibroblasts, melanocytes and Langerhans cells harvested from a small STSG sample for application across the wound surface. In addition, basal layer cells, extracted from the basal lamina, are known to have stem cell‐like characteristics, and may be important contributors to the clinical benefit derived from the cell suspension.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Autologous skin cell suspension enables delivery of viable keratinocytes, fibroblasts, melanocytes and Langerhans cells harvested from a small STSG sample for application across the wound surface. In addition, basal layer cells, extracted from the basal lamina, are known to have stem cell‐like characteristics, and may be important contributors to the clinical benefit derived from the cell suspension.…”
Section: Discussionmentioning
confidence: 99%
“…Autologous skin cell suspension technology is frequently used for acute and chronic wounds as an adjunct to standard skin grafting procedures. The autologous skin cell suspension is produced quickly and is available immediately for wound application.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This may lead to an accelerated resurfacing phase and thus overall improved wound healing quality. For example, it could be demonstrated that the combination of keratinocytes with split‐skin grafts leads to an increased take rate in chronic wounds and less complications concerning wound healing . The use of cultured keratinocytes to support the healing process in complex wounds is also well‐documented .…”
Section: Discussionmentioning
confidence: 99%